Truss Spar Platform Motions for Combined Wave, Current and Wind Forces - V. J. , Kurian (2012)
Truss spar platform is the second development concept that replaces the cylindrical lower section of a classic spar with an open truss structure that includes heave plates. In this paper, the dynamic responses of the Marlin truss spar in regular waves, current and wind are presented. A MATLAB code named TRSPAR was developed for the dynamic analysis of the structure. The structure was modeled as a rigid body with three degrees of freedom. The hyperbolic extrapolation and the extended Morison equation for an inclined cylinder were used for simulating the sea state and for determining the dynamic force vector. Time domain integration using Newmark Beta method was employed. The simulated results show insignificant effect of current and wind on the responses. However, these forces cause significant increase in the surge mean offset.